2021
DOI: 10.31989/ffhd.v11i5.788
|View full text |Cite
|
Sign up to set email alerts
|

Can functional foods reduce the risk of disease? Advancement of functional food definition and steps to create functional food products

Abstract: The definition of functional foods (FFs) has been in development for many years by the Functional Food Scientists of the Functional Food Institute/Functional Food Center (FFC). The status of the FFC’s definition is currently unrecognized by the Food and Drug Administration (FDA),but recognition is important for the safe, uniform development and disbursement of functional food products (FFPs) that could improve the health of Americans and people around the world struggling with chronic and viral diseases. If fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 10 publications
2
98
0
2
Order By: Relevance
“…to Authorize an FFP [2]. A notable example of this challenge is that scientific research has found a beneficial effect of soy isoflavones on the risk of Cardiovascular Disease.…”
Section: Scientific and Methodological Challenges In Functional Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…to Authorize an FFP [2]. A notable example of this challenge is that scientific research has found a beneficial effect of soy isoflavones on the risk of Cardiovascular Disease.…”
Section: Scientific and Methodological Challenges In Functional Foodmentioning
confidence: 99%
“…The foods must have a recommended dosage, be measured using specific biomarkers, and must be studied through various trials before being released to the public. Even after these foods are marketed, scientists will continue to update information about these foods with aftermarket research [2].…”
Section: What It Means For Food To Be a Functional Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a standard definition is important for developing and promoting functional foods and for consumer acceptance of functional food products, because without a definition, they cannot be categorized or regulated formally. In order to expand acceptance, prevent misinformation, and advance functional food as a separate category, the Functional Food Center (FFC) currently defines functional foods as "natural or processed foods that contain biologically-active compounds; which, in defined, effective, non-toxic amounts, provide a clinically proven and documented health benefit utilizing specific biomarkers, to promote optimal health and reduce the risk of chronic/viral diseases and manage their symptoms'' [1]. Furthermore, Dr.…”
Section: Introductionmentioning
confidence: 99%
“…Martirosyan of the FFC has outlined 15 steps for the development of functional food products and for bringing them to the market [1]. This is a long process, but if widely recognized, can serve as a guide to functional food scientists, researchers, and companies around the world.…”
Section: Introductionmentioning
confidence: 99%